Breaking Paradigms: a Multisite Perspective of the Migratory Phenomenon in Mexico and Central America, 2010-2022 - Rodríguez López , María Teresa (2024)
The migratory phenomenon that crosses Mexico integrates diverse flows that no longer originate only from Central America, but also include people from South America and the Caribbean, as well as those of extra-continental origin; they have in common the predominant intention to reach the United States of America and to confront situations of blockade and high violence on their way. The findings presented here are based on the contributions of the members of a working group committed to research in different areas of the region: Costa Rica, the Guatemala-Mexico border, southern Veracruz, Mexico City and Tijuana, Baja California. The comparative and collaborative method was used, with the systematic exchange of results, methods and references, even shared field stays, to explore the correspondences and dissonances between expressions of the same phenomenon in different contexts. In this way, we were able to analyze how actors and spaces of migration are constituted, and how each context potentiates certain processes (securitization, militarization, vertical border, racialization, entrapment) that together redraw the global migratory field.